Al-Ṣumūd wa al-takayyuf wa al-tathāquf: Ta‘bīr ‘an huwīyat al-‘ulamā’ fī al-manfá bi Kampung Jawa Tondano - Achmad Syahid (Studia Islamika, 2017)
The disturbing, destructive and detrimental religious-political relations between Muslim warriors, kings or sultans, princes, and the santri Muslims in the archipelago during the VOC and Dutch colonial era, were not the same throughout Indonesia. Islamic relations with colonial rulers with high tension and heating up, perceived by Muslims as jihad not only because of the despotic ruler factor but also because of non-Muslim factor. The case of Kampung Jawa Tondano, Minahasa, provides evidence that the three-party social-religious relation, namely Muslim-Christian-colonial ruler, is unlike in other parts of Indonesia. This study came to the conclusion that the Muslim warriors in Kampung Jawa Tondano have a good ability in adaptation, acculturation and resilience while still embracing Islam, performing rituals, keep their religious identity and traditions in their daily life, but maintaining good relations with Christians despite refusing to accommodate with the Dutch.DOI: 10.15408/sdi.v24i3.6173